Christianity’s Sinicization: What Has Been and What Lies Ahead: Denominational and Theological Thought Development - ZHANG Zhenghao; ZHOU Fuchu (Journal of Research for Christianity in China (JRCC), 2025)
Director Zhuo Xinping of the Chinese Academy of Social Sciences proposed the concept of “Christian Sinicization.” ‘Sinicization’ places greater emphasis on adapting to China’s current cultural, social, and political context than concepts such as localization, indigenization, or contextualization. After the founding of the People’s Republic of China, Chinese Christianity practiced the Three-Self Policy. However, as Wu Yaozong once remarked, “So-called self-propagation is not merely a question of ‘who propagates,’ but more fundamentally, ‘what is propagated.’” Even in the “post-denominational era,” denominational issues persist within Chinese Christianity because the theological ideas of original denominations continue to dominate the content of “what is being preached.” Therefore, the primary task of Christian Sinicization is theological development. Many Chinese scholars, such as Zhao Zichen, Xie Fuyi, and Ding Guangxun, have dedicated themselves to theological development. However, a complete theological system has yet to be formed, nor has it been fully implemented in church practice. This paper also examines the theological thought and church practices of local theologians such as Jia Yuming, Wang Mingdao, and Ni Tuosheng. The theological foundations for “Sinicization” developed by these predecessors and their proven “non-denominational” church practices offer valuable references for today’s Christian “Sinicization” efforts.